La créativité des concepteurs-rédacteurs : publicité digitale et communication environnementale - Didier Courbet; Marie-Pierre Fourquet-Courbet; Séverine Halimi-Falkowicz (Communiquer, 2017)
Despite the significant presence of persuasive communication messages little empirical research has studied the cognitive processes underlying their creation. Lying on a theoretical frame, based on creativity models, cognition and social representations, this exploratory qualitative research aims to better understand the creation processes of two different French populations of “creative”. Namely, creators of digital advertising and creators of environmental communication campaign. The results show similarities and differences between the two populations in regards of the creative cognitive processes and in the metacognitive reflexivity. For example, advertisers are more reflexive and can describe in detail how they “hear intrapsychic voices and dialogue with them in working memory”. In each population, there are two subcultures with different aesthetic and semiotic practices and standards, but all creatives seem to share three types of social representations and the same overestimation bias: a) of the power of the messages they conceived and b) of the truthfulness of their social representations.